21cm Cosmology. Issue Volume 10:Issue S306(2014) (1st July 2015) - Santos, Mario G.; Alonso, David; Bull, Philip; Camera, Stefano; Ferreira, Pedro G.
Abstract: A new generation of radio telescopes with unprecedented capabilities for astronomy and fundamental physics will be in operation over the next few years. With high sensitivities and large fields of view, they are ideal for cosmological applications. We discuss their uses for cosmology focusing on the observational technique of HI intensity mapping, in particular at low redshifts ( z < 4). This novel observational window promises to bring new insights for cosmology, in particular on ultra-large scales and at a redshift range that can go beyond the dark energy domination epoch. In terms of standard constraints on the dark energy equation of state, telescopes such as Phase I of the SKA should be able to obtain constrains about as well as a future galaxy redshift surveys. Statistical techniques to deal with foregrounds and calibration issues, as well as possible systematics are also discussed.